Sculpt with Optra Pad : A case report - Maiti, Niladri; Das, Utpal Kumar (Journal of Oral and Dental Sciences, 2013)
Because of the socioeconomic status of the patients, direct resin composite laminate veneers were used to improve the esthetics of their maxillary and mandibular anterior teeth. Laminate veneers are restorations which are envisioned to correct existing abnormalities, esthetic deficiencies and discolorations This case report reflects the use of a innovative composite sculpting instrument ( OPTRA SCULPT PAD) for direct composite laminate in a patient who came with complaint of broken old laminate.